Flame-retardant heat-conduction-resistant two-component polyurethane structural adhesive for new energy lithium battery

By modifying the main components of the two-component polyurethane structural glue and introducing modified alumina and magnesium hydroxide composite materials, the problems of low tensile strength, poor flame retardancy and thermal conductivity need to be improved in the existing structural glue are solved, and the high tensile strength, good flame retardancy and excellent thermal conductivity of structural glue are achieved.

CN119842358AActive Publication Date: 2025-04-18BOSEN NEW MATERIALS (YANTAI) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510336091.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-04-18
Estimated Expiration
2045-03-21

AI Technical Summary

Technical Problem

The existing two-component polyurethane structural adhesives have problems such as low tensile strength, poor flame retardancy and thermal conductivity that need to be improved, which affects its application in new energy lithium batteries.

Method used

By modifying diphenylmethane diisocyanate and introducing functional fillers such as modified alumina and magnesium hydroxide composite materials, flame retardant and heat-resistant two-component polyurethane structural glue for new energy lithium batteries was prepared.

Benefits of technology

It effectively improves the tensile strength of structural glue, increases the thermal conductivity, and obtains good flame retardancy, and is suitable for the application of new energy lithium batteries.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and particularly relates to a flame-retardant heat-conduction-resistant two-component polyurethane structural adhesive for a new energy lithium battery. The flame-retardant heat-conduction-resistant bi-component polyurethane structural adhesive for the new energy lithium battery is prepared by modifying the main component diphenylmethane diisocyanate of the bi-component polyurethane structural adhesive and introducing functional fillers such as a modified aluminum oxide and magnesium hydroxide composite material, so that the tensile strength of the structural adhesive is effectively improved, and the flame-retardant heat-conduction-resistant bi-component polyurethane structural adhesive is suitable for the new energy lithium battery. The heat conductivity coefficient is increased, and meanwhile, good flame retardance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and specifically relates to a flame-retardant and heat-conductive two-component polyurethane structural adhesive for new energy lithium batteries. Background Art

[0002] In recent years, with the continuous improvement of my country's new energy vehicle industry chain, new energy vehicles have been booming and sales have increased rapidly. At present, most of the power batteries of new energy vehicles are lithium-ion batteries. The lithium-ion batteries in the car battery pack will generate heat during the charging and discharging process. If this heat cannot be removed in time, it will accumulate inside the battery, causing the battery temperature to be too high, which will not only reduce the battery performance and life, but also cause safety hazards and even lead to serious consequences such as fire. Two-component polyurethane structural adhesive has the characteristics of light weight, high toughness, good insulation, vibration resistance and vibration reduction. It is currently being used in the combination and installation stages of power batteries in more and more new energy vehicles to achieve structural bonding and sealing.

[0003] The invention patent with announcement number CN115558457B discloses a two-component polyurethane structural adhesive and its preparation method and application. The castor oil polyol used in the invention has a high ignition point and good stability, which can improve the flame retardant properties of the structural adhesive; the benzene ring in the aromatic polyether polyol is resistant to moisture and heat, which improves the aging resistance of the structural adhesive; the non-halogenated phosphorus polyol is a phosphorus-containing polyol flame retardant, which has a flame retardant effect, can reduce the amount of flame retardant fillers and small molecule flame retardants added, and achieves lightweight, and does not contain halogen elements, and does not emit a large amount of smoke during combustion, which is environmentally friendly and non-toxic, and the non-halogenated phosphorus polyol participates in the curing reaction to avoid the precipitation of small molecule flame retardants during use. However, the two-component polyurethane structural adhesive in the prior art still has problems such as low tensile strength, poor flame retardancy, and the thermal conductivity needs to be improved, which seriously affects its actual use.

[0004] Therefore, how to modify the components of two-component polyurethane structural adhesive, improve the tensile strength of the structural adhesive, increase the thermal conductivity, obtain good flame retardancy, and apply the structural adhesive to new energy lithium batteries has become a direction that needs to be focused on. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a flame retardant and heat-conductive two-component polyurethane structural adhesive for new energy lithium batteries, aiming to solve the problems of low tensile strength, poor flame retardancy, and the need to improve thermal conductivity of the existing two-component polyurethane structural adhesive.

[0006] The present invention prepares a flame-retardant and heat-resistant two-component polyurethane structural adhesive for new energy lithium batteries by modifying diphenylmethane diisocyanate, a main component of the two-component polyurethane structural adhesive, and introducing functional fillers such as modified alumina and magnesium hydroxide composite materials, thereby effectively improving the tensile strength of the structural adhesive, increasing the thermal conductivity, and obtaining good flame retardancy.

[0007] The technical solution of the present invention is as follows: The present invention provides a flame retardant and heat-conducting two-component polyurethane structural adhesive for new energy lithium batteries, which is composed of component A and component B; In parts by weight, the component A comprises: 20 to 30 parts of a polyurethane prepolymer, 10 to 20 parts of modified diphenylmethane diisocyanate, 50 to 60 parts of aluminum oxide, and 2 to 4 parts of vinyl trimethoxysilane; In parts by weight, the component B comprises: 10 to 20 parts of ricinoleyl alcohol, 10 to 16 parts of polyether polyol, 4 to 8 parts of aldehyde-ketone resin, 60 to 70 parts of magnesium hydroxide, 1 to 3 parts of 3A molecular sieve raw powder, 1.2 to 1.6 parts of triethylamine and 0.6 to 0.8 parts of adhesion promoter; The preparation method of the modified diphenylmethane diisocyanate comprises: firstly coupling 6-12 parts of talc powder by weight, then mixing with 2-6 parts of ethyl acetate, then adding 88-94 parts of diphenylmethane diisocyanate, stirring and dispersing at high speed, and then performing ultrasonic dispersion to obtain the modified diphenylmethane diisocyanate.

[0008] As a preferred technical solution of the present invention, the coupling treatment conditions include: by weight, 80 to 90 parts of anhydrous ethanol and 10 to 20 parts of deionized water are mixed, then 2 to 4 parts of 3-aminopropyltriethoxysilane are added and stirred for 20 to 30 minutes, and then 6 to 12 parts of talc are added and stirred for 30 to 40 minutes, and dried.

[0009] As a preferred technical solution of the present invention, the time for high-speed stirring and dispersing is 10 to 16 minutes, and the time for ultrasonic dispersing is 10 to 20 minutes.

[0010] The talc powder introduced by modified diphenylmethane diisocyanate can be evenly dispersed in the resin matrix after coupling treatment, and the movement of polymer chain segments is restricted by forming physical cross-linking points. This filling effect improves the rigidity and deformation resistance of the material, thereby improving the tensile strength of the structural adhesive.

[0011] As a preferred technical solution of the present invention, the alumina is modified alumina; The preparation method of the modified alumina comprises: adding 90 to 100 parts of pseudo-boehmite to 200 to 240 parts of a boric acid aqueous solution with a mass concentration of 6 to 8% for doping treatment to obtain boron-doped alumina; adding 2 to 4 parts of γ-glycidyloxypropyltrimethoxysilane to 180 to 200 parts of anhydrous ethanol and mixing them evenly, and then adding 90 to 100 parts of the boron-doped alumina for surface treatment to obtain modified alumina.

[0012] As a preferred technical solution of the present invention, the conditions of the doping treatment include: first immersing for 30-40 minutes, then drying at 110-120°C for 50-60 minutes, and finally calcining at 540-550°C for 100-120 minutes.

[0013] As a preferred technical solution of the present invention, the surface treatment conditions include: adjusting the pH to 4.2-4.4, the treatment temperature to 40-50°C, and the treatment time to 2-4h.

[0014] The modified alumina contains boron-doped alumina, which can promote the carbonization reaction of the polymer matrix to form a dense carbon layer, further enhancing the heat insulation and oxygen isolation effects. The presence of the carbon layer not only improves the thermal stability of the material, but also reduces the release of combustible volatiles, thereby improving the flame retardant properties.

[0015] As a preferred technical solution of the present invention, the magnesium hydroxide is a magnesium hydroxide composite material; The preparation method of the magnesium hydroxide composite material comprises: adding 20 to 30 parts of graphene oxide to 100 to 120 parts of deionized water to form a suspension, adding 2 to 4 parts of hydrochloric acid, and then adding 20 to 24 parts of magnesium chloride and 18 to 22 parts of potassium hydroxide for heating reaction to obtain an intermediate product; and mixing 10 to 20 parts of the intermediate product and 10 to 20 parts of 3-aminopropyltriethoxysilane for ball milling to obtain the magnesium hydroxide composite material.

[0016] As a preferred technical solution of the present invention, the conditions of the heating reaction include: first drying at 80-90°C for 1-2 hours, then heat treating at 170-180°C for 4-6 hours, washing with water, and drying.

[0017] As a preferred technical solution of the present invention, the conditions of the ball milling treatment include: ball milling for 4 to 6 hours at a rotation speed of 300 to 400 r / min, washing with acetone, centrifuging for 6 to 10 minutes at a rotation speed of 4000 to 5000 r / min, drying, and grinding.

[0018] The graphene oxide contained in the magnesium hydroxide composite material has excellent two-dimensional thermal conductivity, while magnesium hydroxide provides a good thermal conduction path and thermal stability. The synergistic effect of the two can further optimize the thermal conduction network, thereby significantly improving the thermal conductivity of the structural adhesive.

[0019] As a preferred technical solution of the present invention, the preparation method of the polyurethane prepolymer includes: weighing 90 to 100 parts of polypropylene carbonate diol by weight and heating it to 56 to 60° C., adding 40 to 50 parts of diphenylmethane diisocyanate, heating it to 78 to 80° C. under vacuum conditions, and reacting at a constant temperature for 3 to 4 hours to obtain a polyurethane prepolymer.

[0020] As a preferred technical solution of the present invention, the adhesion promoter is methyltriethoxysilane and 3-aminopropyltriethoxysilane; the mass ratio of methyltriethoxysilane to 3-aminopropyltriethoxysilane in the adhesion promoter is (1~2):1.

[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) The modified diphenylmethane diisocyanate of the present invention contains highly reactive isocyanate groups, which can undergo a ring-opening reaction with the epoxy groups in the modified alumina, and can also undergo a nucleophilic addition reaction with the amino groups introduced into the magnesium hydroxide composite material by 3-aminopropyltriethoxysilane, thereby forming a network interconnected structure, which effectively prevents the initiation and propagation of cracks and thus improves the tensile strength; at the same time, high thermal conductivity fillers such as graphene and alumina are evenly distributed and interconnected in the network interconnected structure, forming a continuous thermal conduction path, thereby improving the thermal conductivity of the material. In addition, the moisture released when the talc in the modified diphenylmethane diisocyanate decomposes can dilute the concentration of combustible gases in the combustion area and reduce the flame propagation speed; the boron-doped alumina of the modified alumina can promote the carbonization reaction of the polymer matrix and form a dense carbon layer, enhancing the heat insulation and oxygen isolation effects; the magnesium hydroxide in the magnesium hydroxide composite material decomposes at high temperature to absorb a large amount of heat, lowering the material temperature, and graphene forms a dense barrier layer on the surface of the material to prevent the penetration of heat and oxygen; the flame retardant properties of the structural adhesive are improved through the synergistic effect of multiple components of talc-boron-doped alumina-magnesium hydroxide-graphene.

[0022] (2) The talc powder introduced by the modified diphenylmethane diisocyanate of the present invention can be evenly dispersed in the resin matrix after coupling treatment, and the movement of the polymer chain segments is restricted by forming physical cross-linking points. This filling effect improves the rigidity and deformation resistance of the material, thereby improving the tensile strength of the structural adhesive.

[0023] (3) The modified alumina of the present invention contains boron-doped alumina, which can promote the carbonization reaction of the polymer matrix to form a dense carbon layer, further enhancing the heat insulation and oxygen isolation effects. The presence of the carbon layer not only improves the thermal stability of the material, but also reduces the release of combustible volatiles, thereby improving the flame retardant properties.

[0024] (4) The graphene oxide contained in the magnesium hydroxide composite material of the present invention has excellent two-dimensional thermal conductivity, while the magnesium hydroxide provides a good thermal conduction path and thermal stability. The synergistic effect of the two can further optimize the thermal conduction network, thereby significantly improving the thermal conductivity of the structural adhesive. DETAILED DESCRIPTION

[0025] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0026] The sources of some components in the embodiments and comparative examples are as follows: Polypropylene carbonate diol, molecular weight 2000g / mol, purchased from Zhongke Jinlong Environmental Protection New Materials Co., Ltd. Commercially available diphenylmethane diisocyanate, brand MDI-100F, was purchased from Wanhua Chemical; Commercially available alumina, product number A406645, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Vinyltrimethoxysilane, CAS No. 2768-02-7, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Ricinoleyl alcohol, product number R341632, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Polyether polyol, brand C2004, purchased from Wanhua Chemical; Aldehyde and ketone resin, product number PA98876, was purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd.; Commercially available magnesium hydroxide, CAS No. 1309-42-8, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; 3A molecular sieve raw powder, model 3A-D-38, purchased from Luoyang Jianlong Micro-Nano New Materials Co., Ltd.; Triethylamine, CAS No. 121-44-8, was purchased from Sinopharm Chemical Reagent Co., Ltd.; N,N-dimethylbenzylamine, CAS No. 103-83-3, purchased from Sinopharm Chemical Reagent Co., Ltd.; Methyltriethoxysilane, CAS No. 2031-67-6, purchased from Sinopharm Chemical Reagent Co., Ltd.; 3-Aminopropyltriethoxysilane, CAS No. 919-30-2, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; γ-Glycidyloxypropyltrimethoxysilane, CAS No. 2530-83-8, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Talc, CAS No. 14807-96-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Ethyl acetate, CAS No. 141-78-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.; 3-Aminopropyltriethoxysilane, CAS No. 919-30-2, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Pseudoboehmite, product number P790504, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Boric acid, CAS No. 10043-35-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.; γ-Glycidyloxypropyltrimethoxysilane, CAS No. 2530-83-8, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Graphene oxide, catalog number G476611, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Hydrochloric acid, CAS No. 7647-01-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Magnesium chloride, CAS No. 7786-30-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Potassium hydroxide, CAS No. 1310-58-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0027] Embodiment 1:

[0028] This embodiment provides a flame retardant and heat-conductive two-component polyurethane structural adhesive for new energy lithium batteries, which consists of component A and component B; In parts by weight, the component A comprises: 30 parts of polyurethane prepolymer, 20 parts of modified diphenylmethane diisocyanate, 60 parts of modified alumina and 4 parts of vinyl trimethoxy silane; In parts by weight, the component B includes: 20 parts of castor oil alcohol, 16 parts of polyether polyol, 8 parts of aldehyde-ketone resin, 70 parts of magnesium hydroxide composite material, 3 parts of 3A molecular sieve raw powder, 1.6 parts of triethylamine and 0.6 parts of adhesion promoter (0.4 parts of methyltriethoxysilane and 0.2 parts of 3-aminopropyltriethoxysilane).

[0029] Preparation of the modified diphenylmethane diisocyanate: In parts by weight, 90 parts of anhydrous ethanol and 20 parts of deionized water are mixed, then 4 parts of 3-aminopropyltriethoxysilane are added and stirred for 30 minutes, then 12 parts of talc are added and stirred for 40 minutes, dried, then mixed with 6 parts of ethyl acetate, then 94 parts of diphenylmethane diisocyanate are added and stirred and dispersed at high speed for 16 minutes, and then ultrasonically dispersed for 20 minutes to obtain the modified diphenylmethane diisocyanate.

[0030] Preparation of the modified alumina: In parts by weight, 100 parts of pseudo-boehmite are added to 240 parts of an aqueous boric acid solution with a mass concentration of 8% for doping treatment, first immersed for 40 minutes, then dried at 120°C for 50 minutes, and finally calcined at 550°C for 100 minutes to obtain boron-doped alumina; 4 parts of γ-glycidyloxypropyltrimethoxysilane are added to 200 parts of anhydrous ethanol and mixed evenly, and then 100 parts of the boron-doped alumina are added for surface treatment (the pH is adjusted to 4.4, the treatment temperature is 50°C, and the treatment time is 2 hours) to obtain modified alumina.

[0031] Preparation of the magnesium hydroxide composite material: by weight, 30 parts of graphene oxide are added to 120 parts of deionized water to form a suspension, 4 parts of hydrochloric acid are first added, and then 24 parts of magnesium chloride and 22 parts of potassium hydroxide are added for heating reaction, first dried at 90° C. for 2 hours, then heat treated at 180° C. for 4 hours, washed with water, and dried to obtain an intermediate product; 20 parts of the intermediate product and 20 parts of 3-aminopropyltriethoxysilane are mixed and ball milled, ball milled for 4 hours at a rotation speed of 400 r / min, washed with acetone, centrifuged at a rotation speed of 5000 r / min for 6 minutes, dried, and ground to obtain the magnesium hydroxide composite material.

[0032] Preparation of the polyurethane prepolymer: 100 parts by weight of polypropylene carbonate diol are weighed and heated to 60° C., 50 parts of diphenylmethane diisocyanate are added, and the temperature is raised to 80° C. under vacuum conditions, and the reaction is carried out at a constant temperature for 3 hours to obtain a polyurethane prepolymer.

[0033] Embodiment 2:

[0034] This embodiment provides a flame retardant and heat-conductive two-component polyurethane structural adhesive for new energy lithium batteries, which consists of component A and component B; In parts by weight, the component A comprises: 20 parts of polyurethane prepolymer, 10 parts of modified diphenylmethane diisocyanate, 50 parts of modified alumina and 2 parts of vinyl trimethoxy silane; In parts by weight, the component B includes: 10 parts of castor oil alcohol, 10 parts of polyether polyol, 4 parts of aldehyde-ketone resin, 60 parts of magnesium hydroxide composite material, 1 part of 3A molecular sieve raw powder, 1.2 parts of triethylamine and 0.8 parts of adhesion promoter (0.4 parts of methyltriethoxysilane and 0.4 parts of 3-aminopropyltriethoxysilane).

[0035] Preparation of the modified diphenylmethane diisocyanate: In parts by weight, 80 parts of anhydrous ethanol and 10 parts of deionized water are mixed, then 2 parts of 3-aminopropyltriethoxysilane are added and stirred for 20 minutes, then 6 parts of talc are added and stirred for 30 minutes, dried, then mixed with 2 parts of ethyl acetate, then 88 parts of diphenylmethane diisocyanate are added and stirred and dispersed at high speed for 10 minutes, and then ultrasonically dispersed for 10 minutes to obtain the modified diphenylmethane diisocyanate.

[0036] Preparation of the modified alumina: by weight, 90 parts of pseudo-boehmite are added to 200 parts of a boric acid aqueous solution with a mass concentration of 6% for doping treatment, first immersed for 30 minutes, then dried at 110°C for 60 minutes, and finally calcined at 540°C for 120 minutes to obtain boron-doped alumina; 2 parts of γ-glycidyloxypropyltrimethoxysilane are added to 180 parts of anhydrous ethanol and mixed evenly, and then 90 parts of the boron-doped alumina are added for surface treatment (adjusting the pH to 4.2, the treatment temperature to 40°C, and the treatment time to 4 hours) to obtain modified alumina.

[0037] Preparation of the magnesium hydroxide composite material: by weight, 20 parts of graphene oxide are added to 100 parts of deionized water to form a suspension, 2 parts of hydrochloric acid are first added, and then 20 parts of magnesium chloride and 18 parts of potassium hydroxide are added for heating reaction, first dried at 80° C. for 2 hours, then heat treated at 170° C. for 6 hours, washed with water, and dried to obtain an intermediate product; 10 parts of the intermediate product and 10 parts of 3-aminopropyltriethoxysilane are mixed and ball milled, ball milled for 6 hours at a rotation speed of 300 r / min, washed with acetone, centrifuged at a rotation speed of 4000 r / min for 10 minutes, dried, and ground to obtain the magnesium hydroxide composite material.

[0038] Preparation of the polyurethane prepolymer: 90 parts by weight of polypropylene carbonate diol are weighed and heated to 56° C., 40 parts of diphenylmethane diisocyanate are added, and the temperature is raised to 78° C. under vacuum conditions, and the reaction is carried out at a constant temperature for 4 hours to obtain a polyurethane prepolymer.

[0039] Embodiment 3:

[0040] This embodiment provides a flame retardant and heat-conductive two-component polyurethane structural adhesive for new energy lithium batteries, which consists of component A and component B; In parts by weight, the component A comprises: 25 parts of polyurethane prepolymer, 15 parts of modified diphenylmethane diisocyanate, 55 parts of modified alumina and 3 parts of vinyl trimethoxy silane; In parts by weight, the component B includes: 15 parts of castor oil alcohol, 12 parts of polyether polyol, 6 parts of aldehyde-ketone resin, 65 parts of magnesium hydroxide composite material, 2 parts of 3A molecular sieve raw powder, 1.4 parts of triethylamine and 0.7 parts of adhesion promoter (0.4 parts of methyltriethoxysilane and 0.3 parts of 3-aminopropyltriethoxysilane).

[0041] Preparation of the modified diphenylmethane diisocyanate: In parts by weight, 85 parts of anhydrous ethanol and 15 parts of deionized water are mixed, and then 3 parts of 3-aminopropyltriethoxysilane are added and stirred for 25 minutes, and then 8 parts of talc are added and stirred for 35 minutes, and then dried, and then mixed with 4 parts of ethyl acetate, and then 90 parts of diphenylmethane diisocyanate are added and stirred and dispersed at high speed for 12 minutes, and then ultrasonically dispersed for 15 minutes to obtain modified diphenylmethane diisocyanate.

[0042] Preparation of the modified alumina: by weight, 95 parts of pseudo-boehmite are added to 220 parts of a boric acid aqueous solution with a mass concentration of 7% for doping treatment, first immersed for 35 minutes, then dried at 115°C for 55 minutes, and finally calcined at 545°C for 110 minutes to obtain boron-doped alumina; 3 parts of γ-glycidyloxypropyltrimethoxysilane are added to 190 parts of anhydrous ethanol and mixed evenly, and then 95 parts of the boron-doped alumina are added for surface treatment (adjusting the pH to 4.3, the treatment temperature to 45°C, and the treatment time to 3 hours) to obtain modified alumina.

[0043] Preparation of the magnesium hydroxide composite material: by weight, 25 parts of graphene oxide are added to 110 parts of deionized water to form a suspension, 3 parts of hydrochloric acid are first added, and then 22 parts of magnesium chloride and 20 parts of potassium hydroxide are added for heating reaction, first dried at 85° C. for 2 hours, then heat treated at 175° C. for 5 hours, washed with water, and dried to obtain an intermediate product; 15 parts of the intermediate product and 15 parts of 3-aminopropyltriethoxysilane are mixed and ball milled, ball milled for 5 hours at a rotation speed of 350 r / min, washed with acetone, centrifuged at a rotation speed of 4500 r / min for 8 minutes, dried, and ground to obtain the magnesium hydroxide composite material.

[0044] Preparation of the polyurethane prepolymer: 95 parts of polypropylene carbonate diol are weighed and heated to 58° C., 45 parts of diphenylmethane diisocyanate are added, and the temperature is raised to 79° C. under vacuum conditions, and the reaction is carried out at a constant temperature for 4 hours to obtain a polyurethane prepolymer.

[0045] Comparative Example 1: The difference between this comparative example and Example 1 is that commercially available diphenylmethane diisocyanate (brand name MDI-100F) is used instead of modified diphenylmethane diisocyanate, commercially available alumina (product number A406645) is used instead of modified alumina, and commercially available magnesium hydroxide (CAS number 1309-42-8) is used instead of the magnesium hydroxide composite material.

[0046] Comparative Example 2: The difference between this comparative example and comparative example 1 is that modified diphenylmethane diisocyanate is used instead of commercially available diphenylmethane diisocyanate (brand number MDI-100F).

[0047] Comparative Example 3: The difference between this comparative example and comparative example 1 is that a magnesium hydroxide composite material is used instead of commercially available magnesium hydroxide (CAS No. 1309-42-8).

[0048] Comparative Example 4: The difference between this comparative example and Example 1 is that commercially available diphenylmethane diisocyanate (brand name MDI-100F) is used instead of modified diphenylmethane diisocyanate.

[0049] Comparative Example 5: The difference between this comparative example and Example 1 is that commercially available alumina (product number A406645) is used instead of modified alumina.

[0050] Comparative Example 6: The difference between this comparative example and Example 1 is that commercially available magnesium hydroxide (CAS No. 1309-42-8) is used to replace the magnesium hydroxide composite material.

[0051] The performance of the two-component polyurethane structural adhesive provided in the above embodiments and comparative examples was tested, and the testing method was as follows: (1) Tensile strength test: refer to the requirements of GB / T 528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber for testing.

[0052] (2) Flame retardancy test: Test in accordance with the requirements of GB / T 2408-2021 Horizontal and vertical methods for determination of combustion performance of plastics.

[0053] (3) Thermal conductivity test: Test according to the requirements of ASTM D5470-17 Standard Test Method for Thermal Conductivity of Thermally Conductive Insulating Materials.

[0054] The above performance test data is shown in Table 1.

[0055] Table 1 Performance test results data table Tensile strength MPa Flame retardant Thermal conductivity W / (m·K) Example 1 14.4 V0 2.08 Example 2 13.9 V0 2.01 Example 3 14.1 V0 2.05 Comparative Example 1 9.5 V1 0.86 Comparative Example 2 11.2 V1 0.89 Comparative Example 3 9.8 V1 1.37 Comparative Example 4 12.4 V1 1.81 Comparative Example 5 12.1 V1 1.78 Comparative Example 6 12.6 V1 1.83 From the above content, it can be seen that the present invention prepares flame-retardant and heat-resistant two-component polyurethane structural adhesive for new energy lithium batteries (Example 1 to Example 3) by modifying the main component of the two-component polyurethane structural adhesive, diphenylmethane diisocyanate, and introducing functional fillers such as modified alumina and magnesium hydroxide composite materials. The tensile strength is 13.9~14.4MPa, the flame retardant grade is V0, and the thermal conductivity is 2.01~2.08W / (m·K).

[0056] Compared with Example 1, commercially available diphenylmethane diisocyanate (brand name MDI-100F) is used instead of modified diphenylmethane diisocyanate, commercially available alumina (article number A406645) is used instead of modified alumina, and commercially available magnesium hydroxide (CAS number 1309-42-8) is used instead of magnesium hydroxide composite material, then the tensile strength is reduced, the flame retardancy is deteriorated, and the thermal conductivity is reduced (Comparative Example 1); Compared with Comparative Example 1, modified diphenylmethane diisocyanate is used instead of commercially available diphenylmethane diisocyanate (brand name MDI-100F), then the tensile strength is increased (Comparative Example 2); Compared with Comparative Example 1, magnesium hydroxide composite material is used instead of commercially available magnesium hydroxide (CAS number 1309-42-8), the thermal conductivity increases (Comparative Example 3); compared with Example 1, commercially available diphenylmethane diisocyanate (brand name MDI-100F) is used instead of modified diphenylmethane diisocyanate, the tensile strength is reduced, the flame retardancy is deteriorated, and the thermal conductivity is reduced (Comparative Example 4); compared with Example 1, commercially available alumina (article number A406645) is used instead of modified alumina, the tensile strength is reduced, the flame retardancy is deteriorated, and the thermal conductivity is reduced (Comparative Example 5); compared with Example 1, commercially available magnesium hydroxide (CAS No. 1309-42-8) is used instead of the magnesium hydroxide composite material, the tensile strength is reduced, the flame retardancy is deteriorated, and the thermal conductivity is reduced (Comparative Example 6).

[0057] In summary, the present invention prepares a flame-retardant and heat-resistant two-component polyurethane structural adhesive for new energy lithium batteries by modifying the main component of the two-component polyurethane structural adhesive, diphenylmethane diisocyanate, and introducing functional fillers such as modified alumina and magnesium hydroxide composite materials, which effectively improves the tensile strength of the structural adhesive, increases the thermal conductivity, and obtains good flame retardancy.

Claims

1. A flame retardant and heat-conductive two-component polyurethane structural adhesive for new energy lithium batteries, characterized in that: It is composed of component A and component B; In parts by weight, the component A comprises: 20 to 30 parts of a polyurethane prepolymer, 10 to 20 parts of modified diphenylmethane diisocyanate, 50 to 60 parts of aluminum oxide, and 2 to 4 parts of vinyl trimethoxysilane; In parts by weight, the component B comprises: 10 to 20 parts of ricinoleyl alcohol, 10 to 16 parts of polyether polyol, 4 to 8 parts of aldehyde-ketone resin, 60 to 70 parts of magnesium hydroxide, 1 to 3 parts of 3A molecular sieve raw powder, 1.2 to 1.6 parts of triethylamine and 0.6 to 0.8 parts of adhesion promoter; The preparation method of the modified diphenylmethane diisocyanate comprises: firstly coupling 6-12 parts of talc powder by weight, then mixing with 2-6 parts of ethyl acetate, then adding 88-94 parts of diphenylmethane diisocyanate, stirring and dispersing at high speed, and then performing ultrasonic dispersion to obtain the modified diphenylmethane diisocyanate.

2. The flame-retardant and heat-conductive two-component polyurethane structural adhesive for new energy lithium batteries according to claim 1, characterized in that: The coupling treatment conditions include: by weight, mixing 80-90 parts of anhydrous ethanol and 10-20 parts of deionized water, then adding 2-4 parts of 3-aminopropyltriethoxysilane and stirring for 20-30 minutes, then adding 6-12 parts of talc and stirring for 30-40 minutes, and drying.

3. The flame-retardant and heat-conductive two-component polyurethane structural adhesive for new energy lithium batteries according to claim 1, characterized in that: The aluminum oxide is modified aluminum oxide; The preparation method of the modified alumina comprises: adding 90 to 100 parts of pseudo-boehmite to 200 to 240 parts of a boric acid aqueous solution with a mass concentration of 6 to 8% for doping treatment to obtain boron-doped alumina; adding 2 to 4 parts of γ-glycidyloxypropyltrimethoxysilane to 180 to 200 parts of anhydrous ethanol and mixing them evenly, and then adding 90 to 100 parts of the boron-doped alumina for surface treatment to obtain modified alumina.

4. The flame-retardant and heat-conductive two-component polyurethane structural adhesive for new energy lithium batteries according to claim 3, characterized in that: The doping treatment conditions include: first dipping for 30-40 minutes, then drying at 110-120° C. for 50-60 minutes, and finally calcining at 540-550° C. for 100-120 minutes.

5. The flame-retardant and heat-conductive two-component polyurethane structural adhesive for new energy lithium batteries according to claim 3, characterized in that: The surface treatment conditions include: adjusting the pH to 4.2-4.4, the treatment temperature to 40-50° C., and the treatment time to 2-4 hours.

6. The flame-retardant and heat-conductive two-component polyurethane structural adhesive for new energy lithium batteries according to claim 1, characterized in that: The magnesium hydroxide is a magnesium hydroxide composite material; The preparation method of the magnesium hydroxide composite material comprises: adding 20 to 30 parts of graphene oxide to 100 to 120 parts of deionized water to form a suspension, adding 2 to 4 parts of hydrochloric acid, and then adding 20 to 24 parts of magnesium chloride and 18 to 22 parts of potassium hydroxide for heating reaction to obtain an intermediate product; and mixing 10 to 20 parts of the intermediate product and 10 to 20 parts of 3-aminopropyltriethoxysilane for ball milling to obtain the magnesium hydroxide composite material.

7. The flame-retardant and heat-conductive two-component polyurethane structural adhesive for new energy lithium batteries according to claim 6, characterized in that: The conditions of the heating reaction include: first drying at 80-90° C. for 1-2 hours, then heat treating at 170-180° C. for 4-6 hours, washing with water, and drying.

8. The flame-retardant and heat-conductive two-component polyurethane structural adhesive for new energy lithium batteries according to claim 6, characterized in that: The ball milling treatment conditions include: ball milling for 4 to 6 hours at a rotation speed of 300 to 400 r / min, washing with acetone, centrifuging for 6 to 10 minutes at a rotation speed of 4000 to 5000 r / min, drying, and grinding.

9. The flame-retardant and heat-conductive two-component polyurethane structural adhesive for new energy lithium batteries according to claim 1, characterized in that: The preparation method of the polyurethane prepolymer comprises: weighing 90-100 parts of polypropylene carbonate diol by weight, heating the mixture to 56-60° C., adding 40-50 parts of diphenylmethane diisocyanate, heating the mixture to 78-80° C. under vacuum conditions, and reacting the mixture at a constant temperature for 3-4 hours to obtain the polyurethane prepolymer.

10. The flame-retardant and heat-conductive two-component polyurethane structural adhesive for new energy lithium batteries according to claim 1, characterized in that: The adhesion promoter is methyltriethoxysilane and 3-aminopropyltriethoxysilane; the mass ratio of methyltriethoxysilane to 3-aminopropyltriethoxysilane in the adhesion promoter is (1~2):1.

Citation Information

Patent Citations

  • A two-component polyurethane structural adhesive, its preparation method and application

    CN115558457B

  • Bi-component polyurethane structural adhesive as well as preparation method and application thereof

    CN115558457A

  • Low-density bi-component polyurethane heat-conducting structural adhesive for power battery and preparation method of low-density bi-component polyurethane heat-conducting structural adhesive

    CN115873553A

  • Polyurethane structural adhesive with low specific gravity and high thermal conductivity and preparation method thereof

    CN116265558A

  • High-flame-retardant bi-component polyurethane heat-conducting structural adhesive as well as preparation method and application thereof

    CN118496804A